Academic Writing of EFL Students’ Undergraduate Theses: A Discourse Marker Analysis - Marcellina Haninda; Barli Bram (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
Writing the background is obligatory in undergraduate theses, and discourse markers are essential to creating cohesion and coherence in academic writing. Thus, this paper aimed to investigate discourse markers used by the undergraduate students in writing their thesis backgrounds and the extent of accuracy of the use of DMs in the students’ thesis backgrounds. Data were collected from 28 undergraduate thesis backgrounds written by the students of the English Language Education Study Program of Sanata Dharma University, Yogyakarta batch 2016, who graduated between May 2020 and January 2021. Descriptive research was employed, and the data were examined using document analysis. Results showed that elaborative markers were used 763 times (74.58%) and followed by reason markers 95 times (9.29%), inferential markers 85 times (8.31%), and contrastive markers 80 times (7.82%). In general, the EFL students used DMs accurately in their thesis backgrounds. Some DMs were, however, used inappropriately. It is essential that the EFL students better understand how to use DMs appropriately when writing their thesis backgrounds.